ER Import Sites and Their Relationship to ER Exit Sites: A New Model for Bidirectional ER-Golgi Transport in Higher Plants - Lerich, Alexander; Hillmer, Stefan; Langhans, Markus; Scheuring, David; van Bentum, Paulien; Robinson, David G. (Frontiers in Plant Science, 2012)
The plant Golgi apparatus is polydisperse and COPII fluorescence localizes to the interface between the ER and the overlying Golgi stack rather than the surface of the ER. Per definition, ER exit sites (ERES) are COPII vesiculation events at the surface of the ER and are only visualizable in the electron microscope through cryofixation techniques. Nevertheless, ERES is always associated with Golgi stacks and both move together. We have asked whether the domain of the ER where retrograde COPI vesicles fuse, i.e. ER import sites, (ERIS), is also coupled to Golgi stack motility and therefore spatially associated with ERES? As ERIS markers we have investigated ER-located SNAREs and tethering factors. We screened several SNAREs (SYP81, the SYP7 family, and USE1) to find a SNARE whose overexpression did not disrupt ER-Golgi traffic and which gave rise to discrete fluorescent punctae when expressed with an XFP tag. Only the Qc SNARE SYP72 fulfilled these criteria, and, based on quantitative protein transport assays with the retrograde reporter α-amylase-HDEL, even appeared to enhance retrograde traffic. When coexpressed with SYP72-YFP, the type I membrane protein RFP-p24δ5 whose ER localization is due to an efficient COPI-mediated recycling, forms nodules along the tubular ER network. SYP72 colocalizes with these nodules which are not seen when RFP-p24δ5 is expressed alone or when SYP72-YFP is coexpressed with a mutant form of RFP-p24δ5 that cannot exit the ER. Immobilized Golgi stacks show a perfect colocalization between SYP72-YFP and fluorescent COPII/Golgi markers. Endogenous SYP72, also colocalizes with COPII/Golgi. Fluorescently tagged versions of plant homologs to TIP20 of the Dsl1 COPI-tethering factor complex, and to the COPII-tethering factor p115 both colocalize perfectly with Golgi stacks. These data suggest that ERES, ERIS and Golgi stacks are closely associated thereby constituting a mobile secretory and recycling unit: a unique feature in eukaryotic cells.